VARIATIONS IN ORIGIN OF THE FACIAL ARTERY AND POTENTIAL CLINICAL CONSEQUENCES - REVIEW OF THE LITERATURE - Victor Nimigean; Renata Cernătescu; Alexandru Poll; Vanda Roxana Nimigean; Maria Justina Roxana Vîrlan; Valentin Daniel Sîrbu; Simona Andreea Moraru (Romanian Society of Oral Rehabilitation, 2019)
Aim of the study: The purpose of the study is to document in the specialised literature the variations in origin of the facial artery (FA) at the level of the carotid triangle. Material and methods: we analysed 89 summaries of scientific papers and 41 complete articles, using ISI Thomson Web of Knowledge and PubMed databases, and additionally, we performed a search in 9 anatomy books. Results: the most common variation of origin of the facial artery was in the form of a common trunk with the lingual artery, a linguofacial trunk, with an average percentage of 16.39% of the cases. A rare variation of origin of the facial artery was the thyrolinguofacial trunk with an average percentage of 2.1% of the cases. The results observed were mostly unilateral, but many publications did not present observations regarding the unilateral or bilateral nature of these origins. Conclusions: the results depict a wide variety of origins of FA from the external carotid artery (ECA) and can contribute to the clinical success of surgical procedures performed in the anterior region of the neck and the face